Powder metallurgy high-temperature-resistant nano-phase strengthened high-entropy alloy and preparation method thereof

CN120290956BActive Publication Date: 2026-10-16CENT SOUTH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510460237.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-14
Publication Date
2026-10-16
Estimated Expiration
2045-04-14

AI Technical Summary

Technical Problem

然而,从成分设计的角度来说,该类高熵合金的等原子比或近等原子比的成分组成不利于获得L12纳米相增强的最佳成分组合,使得材料在高温服役过程中无法维持较高的比强度

Benefits of technology

[0025] (1) The powder metallurgy high temperature resistant nanophase reinforced high entropy alloy of the present invention has FCC and L12 dual-phase structure, has excellent room/high temperature mechanical properties, and is suitable for complex working conditions such as high temperature and high pressure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120290956B_ABST
    Figure CN120290956B_ABST
Patent Text Reader

Abstract

The application discloses a powder metallurgy high-temperature-resistant nano-phase reinforced high-entropy alloy and a preparation method thereof, and belongs to the technical field of metal materials. The powder metallurgy high-temperature-resistant nano-phase reinforced high-entropy alloy comprises Ni and the following raw materials in percentage by mass: Co 22.0-25.9%, Cr 8.0-9.7%, Fe 7.0-8.7%, Ti 3.3-4.5%, Al 3.5-4.9%, Ta 3.0-3.5%, Nb 0.6-1.2%, W 1.3-2.0%, Mo 0.6-1.1%, Hf 0.1-0.3%, Zr 0.01-0.05%, B 0.05-0.3% and inevitable impurities. The powder metallurgy high-temperature-resistant nano-phase reinforced high-entropy alloy has an FCC and L12 dual-phase structure and excellent room / high-temperature mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metallic materials technology, and in particular to a powder metallurgy high-temperature resistant nanophase-reinforced high-entropy alloy and its preparation method. Background Technology

[0002] With the development of aero-engine technology, high-temperature load-bearing structures such as aero-engine blades and combustion chamber casings have stringent requirements for materials in terms of high-temperature strength, toughness, durability, and oxidation resistance. Currently, the development of high-temperature (700–900℃) and high-specific-strength materials for combustion chamber casings is at a bottleneck stage. For example, nickel-based superalloys exhibit good strength, structural stability, and oxidation resistance during long-term service below 750℃, but their specific strength (tensile strength / density) is relatively low, and they suffer from mid-temperature grain boundary brittleness (e.g., the ductility of U720Li superalloy drops sharply from over 15% to 3% at 750℃), which will affect the reliability of aero-engine performance. While second-generation TiAl alloys, which have been applied abroad, have low density and high specific strength, they are brittle at room temperature, making it difficult to exceed 750℃ in operating temperatures. Third-generation TiAl alloys for temperatures above 800℃ are still under development, and their room-temperature brittleness and high-temperature structural stability issues remain unresolved. Based on these circumstances, the development of new high-performance high-temperature structural materials with high thermal stability and high strength and toughness is particularly urgent.

[0003] Compared to traditional nickel-based / cobalt-based superalloys, high-entropy alloys possess superior room / high-temperature mechanical properties and functional characteristics due to their strong high-entropy effect, lattice distortion effect, diffusion hysteresis effect, and interactions between multiple principal elements. They hold great application potential in complex high-temperature structural components such as military aero-engines. Currently, the widely studied single-phase FCC structure FeCoCrNi-based high-entropy alloys typically exhibit good ductility, but their strength is relatively low, making it difficult to meet the performance requirements of advanced high-temperature structural materials.

[0004] Introducing tough nanoparticles for second-phase dispersion strengthening is an important means of improving material strength (especially high-temperature strength). L12-type nanophase-reinforced high-entropy alloys combine the advantages of a high-entropy matrix and nanophase reinforcement, overcoming the strength-plasticity imbalance problem of single-solid-solution high-entropy alloys and achieving a better balance of strength and toughness at both room and high temperatures. However, from a compositional design perspective, the equiatomic or near-equiatomic ratio composition of these high-entropy alloys is not conducive to obtaining the optimal compositional combination for L12 nanophase reinforcement, making it difficult for the material to maintain high specific strength during high-temperature service. Therefore, developing alloy materials with low density and excellent room / high-temperature performance is an important goal for promoting applications in high-temperature engineering. Summary of the Invention

[0005] The purpose of this invention is to provide a powder metallurgy high-temperature resistant nanophase-reinforced high-entropy alloy and its preparation method, so as to solve the problems existing in the prior art.

[0006] To achieve the above objectives, the present invention provides the following solution:

[0007] One of the technical solutions of the present invention is a powder metallurgy high-temperature resistant nanophase-reinforced high-entropy alloy, comprising, by mass percentage, Ni and the following raw materials: Co 22.0-25.9%, Cr 8.0-9.7%, Fe 7.0-8.7%, Ti 3.3-4.5%, Al 3.5-4.9%, Ta 3.0-3.5%, Nb 0.6-1.2%, W 1.3-2.0%, Mo 0.6-1.1%, Hf 0.1-0.3%, Zr 0.01-0.05%, B 0.05-0.3%, and unavoidable impurities.

[0008] The second technical solution of the present invention: a method for preparing the above-mentioned powder metallurgy high-temperature resistant nanophase reinforced high-entropy alloy, comprising the following steps:

[0009] Weigh the raw materials (such as intermediate alloys FeW and TiTa) by mass percentage, mix them, melt and grind them into powder to obtain alloy powder;

[0010] The alloy powder is pressed to obtain a bulk material;

[0011] The bulk material is heat-treated to obtain the powder metallurgy high-temperature resistant nanophase reinforced high-entropy alloy.

[0012] Furthermore, the powder preparation method includes gas atomization powder preparation; the gas atomization powder preparation is carried out under a protective atmosphere.

[0013] Furthermore, the pressing method includes hot isostatic pressing;

[0014] The hot isostatic pressing specifically includes: heating to 700-900℃ at a heating rate of 8-15℃ / min in an environment with a vacuum degree ≤0.4Pa, then heating to 1100-1300℃ at a heating rate of 4-8℃ / min and holding at that temperature for 60-300min, while applying a pressure of 100-200MPa during the hot isostatic pressing process.

[0015] Furthermore, the heat treatment includes: first performing a solution treatment, and then performing an intermediate heat treatment.

[0016] Furthermore, the solution treatment temperature is 1150–1250°C, and the holding time is 12–25 h.

[0017] Furthermore, the intermediate heat treatment temperature is 780–920°C, and the holding time is 25–50 h.

[0018] The third technical solution of the present invention: the application of the above-mentioned powder metallurgy high-temperature resistant nanophase reinforced high-entropy alloy in the preparation of aero-engines or gas turbines.

[0019] The powder metallurgical high-temperature resistant nanophase-reinforced high-entropy alloy of this invention, by controlling the mass percentage of Ni to be 39.8-46.0%, Co to be 22.0-25.9%, and Fe to be 7.0-8.7%, can stabilize the face-centered cubic matrix. Simultaneously, by adding 3.5-4.9% Al and 3.3-4.5% Ti by mass, a high-density L12 precipitate can be obtained. After precipitation hardening (i.e., heat treatment below the L12 phase dissolution temperature to precipitate a high volume fraction of L12 phase), the alloy can maintain a stable L12 phase at both room temperature and high temperature (acting as precipitation strengthening). Furthermore, the higher Al content facilitates the formation of an alumina film, thereby improving oxidation resistance. Through doping... A fixed amount of Cr (8.0–9.7%) forms a dense chromium oxide film, further improving the alloy's high-temperature hot corrosion resistance and oxidation resistance. Furthermore, the addition of W (1.3–2.0%), Mo (0.6–1.1%), and Hf (0.1–0.3%) elements strengthens the matrix through solid solution and slows the coarsening kinetics of precipitation. Simultaneously, the addition of these large-size refractory micro-elements increases the degree of lattice distortion in the alloy, which is beneficial for improving the alloy's high-temperature strength (providing high strength and phase stability at high temperatures, ensuring the alloy's creep resistance). Finally, a small amount of B (0.05–0.3%) and Zr (0.01–0.05%) microalloying is used for grain boundary strengthening, thereby significantly improving the alloy's high-temperature strength and creep resistance.

[0020] The alloy of this invention incorporates Ta and Nb elements. Ta and Nb not only act as solid solution strengthening atoms to enhance alloy strength, but also, as L12 phase forming elements, increase the L12 phase content, which is beneficial for improving the alloy's high-temperature strength. However, excessive L12 phase can easily lead to a deterioration in the overall processing performance of the alloy. Furthermore, excessive Ta and Nb elements readily react with elements such as Co and Cr to form Laves phases such as Co2Ta and Cr2Nb, which are detrimental to the alloy's plastic deformation behavior. Therefore, this invention controls the mass percentage of Ta at 3.0–3.5% and the mass percentage of Nb at 0.6–1.2%.

[0021] Adding Nb can also reduce the alloy's susceptibility to hot cracking during the preparation process (such as high undercooling during heat treatment).

[0022] The alloy composed of the above components of this invention has a wide hot working window (370–420°C, within which the alloy will not become unstable and fail) and excellent plasticity. It does not produce significant porosity or cracks during forming, resulting in a high yield. By adding and controlling the content of Ti, Al, Nb, and Ta elements, not only can the age-hardening characteristics be fully utilized, but also the good processing performance of the alloy can be guaranteed, achieving a uniform and dispersed distribution of the L12 phase.

[0023] The powder metallurgical high-temperature resistant nanophase-reinforced high-entropy alloy of this invention combines the plasticity of the FeCoCrNi matrix with the strength of Ni3(Ti,Al) type L12 phase nanoparticles. Through solid solution strengthening and grain boundary strengthening by elements such as Mo, Nb, Ta, Hf, W, Zr, and B, it exhibits a yield strength of 926–940 MPa at 800℃ and a density ≤8.24 g / cm³. 3 It meets the design and usage requirements of advanced aero engines and gas turbines.

[0024] The present invention discloses the following technical effects:

[0025] (1) The powder metallurgy high temperature resistant nanophase reinforced high entropy alloy of the present invention has FCC and L12 dual-phase structure, has excellent room / high temperature mechanical properties, and is suitable for complex working conditions such as high temperature and high pressure.

[0026] (2) The powder metallurgy high-temperature resistant nanophase-reinforced high-entropy alloy of the present invention can achieve a tensile strength of 940 MPa at 800℃, an elongation after fracture of 8.6%, and a density reduced to 8.10 g / cm³. 3 It meets the design and application requirements of advanced aerospace structural materials.

[0027] (3) The powder metallurgy high-temperature resistant nanophase-reinforced high-entropy alloy prepared by this invention has a low alloy density, excellent high-temperature tensile properties, plasticity, and creep resistance. The forming process is free of microcracks and porosity, meeting the design and usage requirements of advanced aero-engines and gas turbines, and can be applied to hot-end components of advanced aero-engines and gas turbines. This alloy not only possesses excellent high-temperature strength but also maintains good plasticity at both room temperature and high temperatures. The forming process is free of microcracks and porosity, exhibiting good processing performance. The forming process is simple and suitable for industrial production and widespread application. Attached Figure Description

[0028] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0029] Figure 1 The images show the XRD pattern and particle size distribution of the alloy powder prepared in Example 1 of this invention, where (a) is the XRD pattern and (b) is the particle size distribution.

[0030] Figure 2 The images show the XRD pattern and scanning electron microscope (SEM) image of the powder metallurgy high-temperature resistant nanophase-reinforced high-entropy alloy prepared in Example 1 of this invention, where (a) is the XRD pattern and (b) is the SEM image.

[0031] Figure 3 Comparison of the mechanical properties of powder metallurgy high-temperature resistant nanophase-reinforced high-entropy alloys prepared in Examples 1-2 and Comparative Examples 1-3 of this invention;

[0032] Figure 4 The diagram shows the oxidation properties of the powder metallurgy high-temperature resistant nanophase-reinforced high-entropy alloy prepared in Example 1 of this invention. Detailed Implementation

[0033] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0034] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0035] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0036] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0037] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0038] Example 1

[0039] A method for preparing a high-entropy high-temperature resistant nanophase-reinforced alloy using powder metallurgy:

[0040] (1) A powder metallurgy high-temperature resistant nanophase-reinforced high-entropy alloy, with the following composition by mass percentage: Co 24.5%, Cr 9.5%, Fe 8.0%, Ti 4.2%, Al 4.0%, Ta 3.2%, Nb 1.0%, W 2.0%, Mo 0.7%, Hf 0.1%, Zr 0.01%, B 0.1%, with the balance being Ni and unavoidable impurities;

[0041] Weigh the raw materials according to the above mass percentages, mix and heat them, and after full melting, perform gas atomization to obtain alloy powder (particle size distribution is mainly between 10 and 100 μm);

[0042] (2) In an environment with a vacuum degree ≤0.4Pa, a stainless steel sheath containing alloy powder is subjected to hot isostatic pressing (first heated to 800℃ at a heating rate of 10℃ / min, then heated to 1200℃ at a heating rate of 8℃ / min, and held for 3h), and a pressure of 200MPa is applied throughout the hot isostatic pressing process to obtain a bulk material with a stainless steel sheath.

[0043] (3) The block material with stainless steel sheath is cut, trimmed and deburred to obtain alloy rod.

[0044] (4) The alloy rod is subjected to a solid solution treatment at 1200℃ for 24 hours to remove the original powder boundary of the alloy and obtain the alloy rod.

[0045] (5) The alloy rods obtained after step (4) are aged at 800℃ for 50 hours to obtain a powder metallurgy high-temperature resistant nanophase reinforced high-entropy alloy.

[0046] The XRD pattern of the alloy powder prepared in this embodiment is shown in the figure. Figure 1 Figure (a) shows the particle size distribution diagram. Figure 1 (b) of the diagram.

[0047] from Figure 1 As can be seen from the data, the alloy powder prepared in this embodiment has a single-phase FCC structure, with a particle size distribution mainly between 10 and 100 μm and an average particle size of 47.6 μm.

[0048] The XRD pattern of the powder metallurgy high-temperature resistant nanophase-reinforced high-entropy alloy prepared in this embodiment is shown below. Figure 2Figure (a) and its scanning electron microscope image are shown below. Figure 2 (b) of the diagram.

[0049] from Figure 2 As can be seen from the above, the powder metallurgy high-temperature resistant nanophase reinforced high-entropy alloy prepared in this embodiment has a dual-phase FCC / L12 structure, with a high-density L12 phase uniformly distributed in the FCC matrix.

[0050] The powder metallurgy high-temperature resistant nanophase reinforced high-entropy alloy obtained in step (5) was processed into dog bone tensile specimens with a gauge length of 8 mm, a width of 3 mm, and a thickness of 2 mm. Tensile tests were conducted on a universal testing machine at a rate of 1 mm / min. The tensile strength at 800℃ was measured to be 940 MPa and the elongation after fracture was 8.6%.

[0051] Example 2

[0052] Same as Example 1, except that step (2) is specifically as follows: in an environment with a vacuum degree ≤0.4Pa, the stainless steel sheath containing alloy powder is subjected to hot isostatic pressing (first heated to 800°C at a heating rate of 10°C / min, then heated to 1100°C at a heating rate of 8°C / min, and held for 3h), and a pressure of 200MPa is applied throughout the hot isostatic pressing process to obtain a block material with a stainless steel sheath.

[0053] The powder metallurgy high-temperature resistant nanophase reinforced high-entropy alloy prepared in this embodiment has a tensile strength of 926 MPa at 800℃ and an elongation after fracture of 8.2%.

[0054] Comparative Example 1

[0055] Same as Example 1, except that the alloy raw material does not contain Ti and Al elements. The powder metallurgy high-temperature resistant nanophase reinforced high-entropy alloy has the following composition by mass percentage: Co 24.5%, Cr 9.5%, Fe 8.0%, Ta 3.2%, Nb 1.0%, W 2.0%, Mo 0.7%, Hf 0.1%, Zr 0.01%, B 0.1%, with the balance being Ni and unavoidable impurities.

[0056] The powder metallurgy high-temperature resistant nanophase reinforced high-entropy alloy prepared in this comparative example has a tensile strength of 161 MPa at 800℃ and an elongation after fracture of 62.9%.

[0057] Comparative Example 2

[0058] Same as Example 1, except that the alloy raw materials do not contain W, Mo and Hf elements. The powder metallurgy high-temperature resistant nanophase reinforced high-entropy alloy has the following composition by mass percentage: Co 24.5%, Cr 9.5%, Fe 8.0%, Ti 4.2%, Al 4.0%, Ta 3.2%, Nb 1.0%, Zr 0.01%, B 0.1%, with the balance being Ni and unavoidable impurities.

[0059] The powder metallurgy high-temperature resistant nanophase reinforced high-entropy alloy prepared in this comparative example has a tensile strength of 725 MPa at 800℃ and an elongation after fracture of 3.1%.

[0060] Comparative Example 3

[0061] Same as Example 1, except that the amounts of Ti and Al are changed. The powder metallurgy high-temperature resistant nanophase reinforced high-entropy alloy has the following composition by mass percentage: Co 24.5%, Cr 9.5%, Fe 8.0%, Ti 7.0%, Al 7.0%, Ta 3.2%, Nb 1.0%, W 2.0%, Mo 0.7%, Hf 0.1%, Zr 0.01%, B 0.1%, with the balance being Ni and unavoidable impurities.

[0062] The powder metallurgy high-temperature resistant nanophase reinforced high-entropy alloy prepared in this comparative example has a tensile strength of 870 MPa at 800℃ and an elongation after fracture of 3.6%.

[0063] The high-temperature tensile properties and densities of the powder metallurgy high-temperature resistant nanophase-reinforced high-entropy alloys prepared in the examples and comparative examples are shown in Table 1 and 2. Figure 3 .

[0064] Table 1 High-temperature tensile properties and density of high-entropy alloys

[0065]

[0066] from Figure 4 As can be seen, the high-entropy alloy prepared in Example 1 has a small mass increment (i.e., mass gain) after being oxidized in air at 700°C or 800°C for 108 hours, indicating that it has excellent oxidation resistance and can meet the requirements for use of the alloy in high-temperature extreme environments.

[0067] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. A powder metallurgy high-temperature resistant nanophase-reinforced high-entropy alloy, characterized in that, The composition by mass percentage is as follows: Co 22.0~25.9%, Cr 8.0~9.7%, Fe 7.0~8.7%, Ti 3.3~4.5%, Al 3.5~4.9%, Ta 3.0~3.5%, Nb 0.6~1.2%, W 1.3~2.0%, Mo 0.6~1.1%, Hf 0.1~0.3%, Zr 0.01~0.05%, B 0.05~0.3%, with the balance being Ni and unavoidable impurities; The powder metallurgy high-temperature resistant nanophase reinforced high-entropy alloy has an FCC and L12 dual-phase structure. The preparation method of the powder metallurgy high-temperature resistant nanophase reinforced high-entropy alloy includes the following steps: Weigh the raw materials according to the mass percentage, mix them, melt and grind them into powder to obtain alloy powder; The alloy powder is pressed to obtain a bulk material; The bulk material is heat-treated to obtain the powder metallurgy high-temperature resistant nanophase reinforced high-entropy alloy. The powder preparation method includes gas atomization powder preparation; The pressing method includes hot isostatic pressing; The hot isostatic pressing specifically includes: under a vacuum degree ≤0.4Pa, first heating to 700~900℃ at a heating rate of 8~15℃ / min, then heating to 1100~1300℃ at a heating rate of 4~8℃ / min and holding at that temperature for 60~300min, and applying a pressure of 100~200MPa during the hot isostatic pressing process; The heat treatment includes: first performing a solution treatment, and then performing an intermediate heat treatment; The solution treatment temperature is 1150~1250℃, and the holding time is 12~25h; The intermediate heat treatment temperature is 780~920℃, and the holding time is 25~50h.

2. The application of the powder metallurgy high-temperature resistant nanophase reinforced high-entropy alloy of claim 1 in the preparation of aero-engines or gas turbines.

Citation Information

Patent Citations

  • Method for producing ni-based super-heat-resistant alloy, and ni-based super-heat-resistant alloy

    WO2020195049A1